CRIMINAL OPPORTUNISM OF CYBER CRIME AS A THREAT TO NATIONAL SECURITY OF UKRAINE - Клименко, Ольга Анатоліївна; Гуцалюк, Михайло Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: to analyze the issues of combating cybercrime during the COVID-19 pandemic and to suggest ways to strengthen cybersecurity in Ukraine. Methods: general philosophical, comparative and phenomenological methods are used in the research process. Results: some types of cybercrimes that should be considered during a coronavirus pandemic have been identified; special attention is paid to social engineering, cyber-fraud, APT-attacks on critical infrastructure; proposals for improving the current legislation, and proposals for combating fraud. Discussion: the need to strengthen international cooperation and improve the current legislation, in particular on electronic evidence, in the conditions of increasing the number and complexity of cybercrimes is substantiated, methods of protection against cybercriminals are proposed. The researchers believe that given that the coronavirus pandemic will not disappear in the near future and the number of remote users will increase, the number of cybercrimes will increase accordingly. The authors conclude that the problem of fraud, particularly in cyberspace, due to its dynamics poses a threat to the development of the information society in Ukraine. In this regard, this trend needs to be covered in the new Cyber Security Strategy of Ukraine. Professional training of relevant specialists of cybercrime units is highly important, as well as the implementation of a system to improve the detection of cybercrime. It will also be useful to provide educational information on cyber hygiene in schools and information campaigns, to combat payment fraud. In addition, the authors recommend detecting and combating fraud: 1) use only proven resources and make sure the name of the required site is correct. One inconspicuous character in the site name in the address bar may indicate that you are on a phishing site; 2) do not pass on your bank card details (especially CVV-code and pin-code) to anyone, because bank employees never ask for such information; 3) it is recommended to always use cash on delivery to eliminate the chances of fraudsters seizing your funds.